2021
DOI: 10.1177/13591045211016527
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of children of health workers during the COVID-19 pandemic: A cross-sectional study

Abstract: Children are exposed to large amounts of information and high levels of stress and anxiety from adults around them, the media, and social communication networks during the Covid-19 period. The purpose of this study was to compare the anxiety and depression levels of the children of health workers following the declaration by the World Health Organization (WHO) of Covid-19 as a global pandemic with those of age-matched children of non-health worker parents. This prospective, case-controlled, cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…During the COVID-19 pandemic lockdown, the percentage of Bangladeshi children who suffered from mental health disturbances ranged from 43% for subthreshold disturbances to 7.2% for severe disturbances ( Yeasmin et al., 2020 ). In Turkey, children of health workers had significantly higher anxiety levels measured using the State-Trait Anxiety Inventory for Children (STAI-C) than non-health workers’ children ( Almis et al., 2022 ). In Ireland, a qualitative study showed that adolescents and children experienced increased rates of social isolation, maladaptive behavior, anxiety, and depression during the pandemic ( O'Sullivan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic lockdown, the percentage of Bangladeshi children who suffered from mental health disturbances ranged from 43% for subthreshold disturbances to 7.2% for severe disturbances ( Yeasmin et al., 2020 ). In Turkey, children of health workers had significantly higher anxiety levels measured using the State-Trait Anxiety Inventory for Children (STAI-C) than non-health workers’ children ( Almis et al., 2022 ). In Ireland, a qualitative study showed that adolescents and children experienced increased rates of social isolation, maladaptive behavior, anxiety, and depression during the pandemic ( O'Sullivan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the study also found a significant difference between the two groups of children regarding anxiety levels, with the children whose parents were healthcare workers experiencing more anxiety. These findings are critical because they show that children whose parents work in highly risky settings are at greater risk compared with other children 16 …”
Section: Discussionmentioning
confidence: 99%
“…4,6,[9][10][11][12][13][14][15] However, only a few studies that inform about changes in children's physical, psychological, and developmental states were encountered in the related Turkish literature. [16][17][18][19] It is of critical importance to know the implicit consequences of the pandemic on children to support children and families in a more qualified way. In this regard, considering the fact that emotion regulation is the leading dimension of psychological health, this study investigated the emotion regulation competency of children of healthcare workers in terms of various variables during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic lockdown, the percentage of Bangladeshi children who suffered from mental health disturbances ranged from 43% for subthreshold disturbances to 7.2% for severe disturbances [30]. In Turkey, children of health workers had significantly higher anxiety levels measured using the State-Trait Anxiety Inventory for Children (STAI-C) than non-health workers’ children [31]. In Ireland, a qualitative study showed that adolescents and children experienced increased rates of social isolation, maladaptive behavior, anxiety, and depression during the pandemic [32].…”
Section: Introductionmentioning
confidence: 99%